High-dose perioperative atorvastatin and acute kidney injury following cardiac surgery: a randomized clinical trial - Billings, Frederic T. (JAMA, 2016)
IMPORTANCE: Hydroxy-methylglutaryl-coenzyme A reductase inhibitors affect several mechanisms underlying acute kidney injury (AKI). OBJECTIVE: To test the hypothesis that short-term high-dose perioperative atorvastatin would reduce AKI following cardiac surgery DESIGN, SETTING, PARTICIPANTS: Double-blinded, placebo-controlled, randomized trial of adult cardiac surgery patients conducted November 2009 to October 2014 at Vanderbilt University Medical Center INTERVENTION: Statin-naïve patients (n=199) were randomly assigned 80mg atorvastatin the day before surgery, 40mg the morning of surgery, and 40mg daily following surgery (n=102) or matching placebo (n=97). Patients using statins prior to study enrollment (n=416) continued their pre-enrollment statin until the day of surgery, were randomly assigned 80mg atorvastatin the morning of surgery and 40mg the morning after (n=206) or matching placebo (n=210), and resumed their statin on postoperative day 2. MAIN OUTCOME: AKI, defined as 0.3 mg/dl rise in serum creatinine within 48 hours of surgery (AKIN criteria) RESULTS: The DSMB recommended stopping the statin-naïve group due to increased AKI among statin-naïve participants with chronic kidney disease (CKD, estimated glomerular filtration rate <60 ml/min/1.73 m(2)) receiving atorvastatin and then recommended stopping for futility after 615 participants (median age, 67 years; 188 [30.6%] women, and 202 [32.8%] diabetic) completed the study. Among all participants (n=615), AKI occurred in 64 of 308 participants (20.8%) randomized to atorvastatin versus 60 of 307 participants (19.5%) randomized to placebo (risk ratio [RR], 1.06 [95% CI, 0.78–1.46]; P=0.75). Among statin-naïve participants (n=199), AKI occurred in 22 of 102 (21.6%) receiving atorvastatin versus 13 of 97 (13.4%) receiving placebo (RR, 1.61 [0.86–3.01]; P=0.15), and serum creatinine increased 0.11mg/dl (−0.11 to 0.56) (median [10(th) to 90(th) percentile]) in those randomized to atorvastatin versus 0.05 (−0.12 to 0.33) placebo (mean difference, 0.08 mg/dl [95% CI, 0.01–0.15]; P=0.007). Among statin-users (n=416), AKI occurred in 42 of 206 (20.4%) randomized to atorvastatin versus 47 of 210 (22.4%) placebo (RR, 0.91 [0.63–1.32]; P=0.63). In CKD patients (n=179), AKI occurred in 30 of 84 (35.7%) randomized to atorvastatin versus 31 of 95 (32.6%) placebo (RR, 1.09 [0.73–1.65]; P=0.76). In CKD patients naïve to statins (n=36), AKI occurred in 9 of 17 (52.9%) randomized to atorvastatin, versus 3 of 19 (15.8%) placebo (RR, 3.35 [1.12–10.05]; P=0.03), and serum creatinine increased 0.26 (−0.22 to 0.94) versus −0.06 mg/dl (−0.16 to 0.41) (mean difference, 0.28mg/dl [0.02–0.54]; P=0.04). In CKD statin-users (n=143), AKI occurred in 21 of 67 (31.3%) randomized to atorvastatin, versus 28 of 76 (36.8%) placebo (RR, 0.85 [0.54–1.35]; P=0.59). CONCLUSIONS AND RELEVANCE: Among patients undergoing cardiac surgery, high-dose perioperative atorvastatin treatment, compared to placebo administration, did not reduce the risk of AKI overall, among patients naive to statins, or patients already using a statin. These results do not support the initiation of statin therapy to prevent AKI following cardiac surgery. TRIAL REGISTRATION: Clinicaltrials.gov identifier: NCT00791648